Agda Error message : Cannot eliminate type with variable pattern - agda

I was asked to finish one of the recommended question from plfa:
Exercise ⇔≃× (recommended)
Show that A ⇔ B as defined earlier is isomorphic to (A → B) × (B → A).
I know I need to prove some property of equivalence first, and here is my proof:
record _⇔_ (A B : Set) : Set where
field
to : A → B
from : B → A
⇔-refl : ∀ {A : Set} → A ⇔ A
⇔-refl =
record
{ to = λ{x → x}
; from = λ{y → y}
}
⇔-sym : ∀ {A B : Set}
→ A ⇔ B
→ B ⇔ A
⇔-sym A⇔B =
record
{ to = _⇔_.from A⇔B
; from = _⇔_.to A⇔B
}
⇔-trans : ∀ {A B C : Set}
→ A ⇔ B
→ B ⇔ C
→ A ⇔ C
⇔-trans A⇔B B⇔C =
record
{ to = (_⇔_.to B⇔C) ∘ (_⇔_.to A⇔B )
; from = (_⇔_.from A⇔B) ∘ (_⇔_.from B⇔C )
}
And now, from my understanding, I need to prove
⇔≃× : ∀ {A B : Set} → A ⇔ B ≃ (A → B) × (B → A)
So to prove this, we need to prove four sections: "to" "from" "from∘to" "to∘from"
⇔≃× : ∀ {A B : Set} → (A ⇔ B) ≃ ((A → B) × (B → A))
⇔≃× =
record
{ to = λ{ x ⇔ y → ⟨ ( x → y ) , ( y → x ) ⟩ }
; from = ?
; from∘to = ?
; to∘from = ?
}
But when I finish the "to" section, I want to see if it can pass. So I compile and I got this error message:
Cannot eliminate type (A → B) × (B → A) with variable pattern ⇔(did you supply too many arguments?)when checking the clause left hand side.extendedlambda2 x ⇔ y
Can anyone give some explanation on this type of error message?
Thanks in advance

λ{ x ⇔ y → binds three arguments: x, ⇔, and y but the function you're supposed to define only takes one.

Related

Agda How to solve error: failed to solve the following constraints

What is wrong with this code?
EDIT:
I'm sending all the code including dependencies, imports, flags, etc.
I can't figure out where the error might be. I would be very grateful if someone could direct me how to fix this error.
{-# OPTIONS --type-in-type --without-K #-}
module Basic where
Type = Set
data Path {A : Type} : A → A → Type where
id : {M : A} → Path M M
_≃_ : {A : Type} → A → A → Type
_≃_ = Path
infix 9 _≃_
ap : {A B : Type} {M N : A}
(f : A → B) → Path{A} M N → Path{B} (f M) (f N)
ap f id = id
ap≃ : ∀ {A} {B : A → Type} {f g : (x : A) → B x}
→ Path f g → {x : A} → Path (f x) (g x)
ap≃ α {x} = ap (\ f → f x) α
postulate
λ≃ : ∀ {A} {B : A → Type} {f g : (x : A) → B x}
→ ((x : A) → Path (f x) (g x))
I'm getting this error:
Failed to solve the following constraints:
Has bigger sort: _44
piSort _25 (λ _ → Set) = Set
Has bigger sort: _25
Any help?
I didn't get quite the same error, but I got the file to check by annotating A with type Type in the type of λ≃:
postulate
λ≃ : ∀ {A : Type} {B : A → Type} {f g : (x : A) → B x}
→ ((x : A) → Path (f x) (g x))
The error I saw comes about because Agda will usually assume that you might want to use universe polymorphism, and there happens to be nothing else in the type of λ≃ that constrains A to the lowest universe Type.

Why do function composition and application have a dependent implementation in Agda?

Why do function composition (∘) and application ($) have the implementation as available in https://github.com/agda/agda-stdlib/blob/master/src/Function.agda#L74-L76?
Copied here for convenience:
_∘_ : ∀ {a b c}
{A : Set a} {B : A → Set b} {C : {x : A} → B x → Set c} →
(∀ {x} (y : B x) → C y) → (g : (x : A) → B x) →
((x : A) → C (g x))
f ∘ g = λ x → f (g x)
_∘'_ : ∀ {a b c} {A : Set a} {B : Set b} {C : Set c} →
(B → C) → (A → B) → (A → C)
f ∘' g = λ x → f (g x)
_$_ : ∀ {a b} {A : Set a} {B : A → Set b} →
((x : A) → B x) → ((x : A) → B x)
f $ x = f x
_$'_ : ∀ {a b} {A : Set a} {B : Set b} →
(A → B) → (A → B)
f $' x = f x
I initially thought the rationale behind this was that $ would be able to handle higher order types that $' wouldn't be able to handle. For example, consider A=Nat, B=List, f is ::, where B depends on A. But after a lot of testing, I couldn't come up with an example that would show that the implementation of $' is not sufficient. What scenarios does $ handle that $' isn't able to handle? (Similarly, what scenarios does ∘ handle that ∘' doesn't?
open import Agda.Builtin.Nat public
open import Agda.Primitive public
--data List {a} (A : Set a) : Set a where
-- [] : List A
-- _∷_ : (x : A) (xs : List A) → List A
data Vec {a} (A : Set a) : Nat → Set a where
[] : Vec A zero
_∷_ : ∀ {n} (x : A) (xs : Vec A n) → Vec A (suc n)
tail : ∀ {a n} {A : Set a} → Vec A (suc n) → Vec A n
tail (x ∷ s) = s
_$_ : ∀ {a b} {A : Set a} {B : A → Set b} →
((x : A) → B x) → ((x : A) → B x)
f $ x = f x
_$'_ : ∀ {a b} {A : Set a} {B : Set b} →
(A → B) → (A → B)
f $' x = f x
_∘_ : ∀ {a b c}
{A : Set a} {B : A → Set b} {C : {x : A} → B x → Set c} →
(∀ {x} (y : B x) → C y) → (g : (x : A) → B x) →
((x : A) → C (g x))
f ∘ g = λ x → f (g x)
_∘'_ : ∀ {a b c} {A : Set a} {B : Set b} {C : Set c} →
(B → C) → (A → B) → (A → C)
f ∘' g = λ x → f (g x)
Vecc : ∀ {a} → Nat → (A : Set a) → (Set a)
Vecc x y = Vec y x
data Pair {a b} (A : Set a) (B : A → Set b) : Set (a ⊔ b) where
_,_ : (x : A) → (y : B x) → Pair A B
-- Dependent Pair attempt
--fst : ∀ {a b} {A : Set a} {B : A → Set b} → Pair A B → A
--fst (a , b) = a
--
--f : Pair Nat $' Vec Nat
--f = _,_ zero $' []
--
--g : Pair (Pair Nat $' Vec Nat) $' λ x → Nat
--g = _,_ (_,_ zero $' []) $' zero
-- Some other attempt
--f : ∀ {a n} {A : Set a} → Vec A ((suc ∘' suc) n) → Vec A n
--f {a} = tail {a} ∘' tail {a}
-- Vec attempt
--f : ∀ {a} (A : Set a) → (Set a)
--f {a} = Vecc {a} (suc zero) ∘' Vecc {a} (suc zero)
--
--h = f Nat
--
--x : h
--x = (zero ∷ []) ∷ []
-- List attempt
--f : ∀ {a} (A : Set a) → (Set a)
--f {a} = List {a} ∘' List {a}
--
--g : ∀ {a} (A : Set a) → (Set a)
--g {a} = List {a} ∘ List {a}
--
--h = f Nat
--i = g Nat
--
--x : h
--x = (zero ∷ []) ∷ []
∘′ and $′ don't work with dependent functions. You simply didn't try any tests with dependent functions. For f $ x examples, f must be dependent, for f ∘ g, either of the functions must be dependent. Example:
open import Data.Nat
open import Data.Vec
open import Function
open import Relation.Binary.PropositionalEquality
replicate' : {A : Set} → A → (n : ℕ) → Vec A n
replicate' a n = replicate a
refl' : {A : Set}(a : A) → a ≡ a
refl' a = refl
-- fail1 : Vec ℕ 10
-- fail1 = replicate' 10 $′ 10
ok1 : Vec ℕ 10
ok1 = replicate' 10 $ 10
-- fail2 : ∀ n → replicate' 10 n ≡ replicate' 10 n
-- fail2 = refl' ∘′ replicate' 10
ok2 : ∀ n → replicate' 10 n ≡ replicate' 10 n
ok2 = refl' ∘ replicate' 10
One works with dependent functions, the other doesn't, as Andras Kovacs mentioned.
The important difference is that for non-dependent functions stronger proofs can be constructed. For example:
eq : {A B} -> f : (A -> B) -> x y : A -> x == y -> (f x) == (f y)
eq f x .x refl = refl
Here we can construct equality of f x and f y. But we can't do the same for dependent functions - because there is no way to prove B x == B y. So there is only a weaker proof that f x can be "cast" to f y.
transport : {A} {B : A -> Set} -> f : (x : A -> B x) -> x y : A -> x == y -> f x -> f y
transport f x .x refl fx = fx
(Actually, transport is usually defined as B x -> B y, not for a dependent function; but I just can't come up with a better name)

How to convert the J axiom to the fixed-argument form?

I was trying to prove that true ≡ false -> Empty assuming the J axiom. It is defined as:
J : Type
J = forall
{A : Set}
{C : (x y : A) → (x ≡ y) → Set} →
(c : ∀ x → C x x refl) →
(x y : A) →
(p : x ≡ y) →
C x y p
My attempt went like this:
bad : J → true ≡ false -> Empty
bad j e = j Bool (λ { true _ _ => Unit; false _ _ => Empty }) _
Now, to proceed with the proof, I needed a term c : ∀ x -> C x x refl. Since I instantiated C, it becomes c : ∀ x -> (λ { true _ _ => Unit; false _ _ => Empty } x x refl. Then I got stuck. c can't reduce further because we don't know the value of x. I wasn't able to complete this proof. But there is a different version of J:
J' : Type
J' = forall
{A : Set}
{x : A}
{C : (y : A) → (x ≡ y) → Set} →
(c : C x refl) →
(y : A) →
(p : x ≡ y) →
C y p
With this one, this problem is solved, because t can be fixed to be true. This makes the c argument reduce to Unit, which we can provide. My question is: can we convert the former version to the later? That is, can we build a term fix_x : J → J'? Does that hold in general (i.e., can indices be converted to parameters)?
First, regarding true ≡ false -> Empty: this is unprovable if you can only eliminate into Set0 with J, so you need an universe polymorphic or large definition. I write some preliminaries here:
{-# OPTIONS --without-K #-}
open import Relation.Binary.PropositionalEquality
open import Level
data Bool : Set where true false : Bool
data Empty : Set where
record Unit : Set where
constructor tt
JTy : ∀ {i j} → Set _
JTy {i}{j} =
{A : Set i}
(P : (x y : A) → (x ≡ y) → Set j) →
(pr : ∀ x → P x x refl) →
{x y : A} →
(p : x ≡ y) →
P x y p
J : ∀ {i}{j} → JTy {i}{j}
J P pr {x} refl = pr x
J₀ = J {zero}{zero}
Now, transport or subst is the only needed thing for true ≡ false -> Empty:
transp : ∀ {i j}{A : Set i}(P : A → Set j){x y} → x ≡ y → P x → P y
transp P = J (λ x y _ → P x -> P y) (λ _ px → px)
true≢false : true ≡ false → Empty
true≢false e = transp (λ {true → Unit; false → Empty}) e tt
Considering now proving the pointed J' from J, I know about three solutions, and each uses different features from the ambient theory.
The simplest one is to use universes to abstract over the induction motive:
JTy' : ∀ {i j} → Set _
JTy' {i}{j} =
{A : Set i}
{x : A}
(P : ∀ y → x ≡ y → Set j)
(pr : P x refl)
{y : A}
(p : x ≡ y)
→ P y p
JTy→JTy' : (∀ {i j} → JTy {i}{j}) → ∀ {i}{j} → JTy' {i}{j}
JTy→JTy' J {i} {j} {A} {x} P pr {y} e =
J (λ x y e → (P : ∀ y → x ≡ y → Set j) → P x refl → P y e)
(λ x P pr → pr) e P pr
If we only want to use a fixed universe level, then it is a bit more complicated. The following solution, sometimes called "contractible singletons", needs Σ-types, but nothing else:
open import Data.Product
JTy→JTy'withΣ : JTy {zero}{zero} → JTy' {zero}{zero}
JTy→JTy'withΣ J {A} {x} P pr {y} e =
J (λ {(x , r) (y , e) _ → P x r → P y e})
(λ _ px → px)
(J (λ x y e → (x , refl) ≡ (y , e))
(λ _ → refl)
e)
pr
There is a solution which doesn't even need Σ-s, but requires the beta rule for J, which says that J P pr {x} refl = pr x. It doesn't matter whether this rule holds definitionally or just as a propositional equality, but the construction is simpler when it holds definitionally, so let's do that. Note that I don't use any universe other than Set0.
transp₀ = transp {zero}{zero}
transp2 : ∀ {A : Set}{B : A → Set}(C : ∀ a → B a → Set)
{x y : A}(e : x ≡ y){b} → C x b → C y (transp₀ B e b)
transp2 {A}{B} C {x}{y} e {b} cxb =
J₀ (λ x y e → ∀ b → C x b → C y (transp₀ B e b)) (λ _ _ cxb → cxb) e b cxb
JTy→JTy'noΣU : JTy' {zero}{zero}
JTy→JTy'noΣU {A} {x} P pr {y} e =
transp₀ (P y) (J₀ (λ x y e → transp₀ (x ≡_) e refl ≡ e) (λ _ → refl) e)
(transp2 {A} {λ y → x ≡ y} P e pr)
Philosophically, the third version is the most "conservative", since it only assumes J. The addition of the beta rule is not really an extra thing, since it is always assumed to hold (definitionally or propositionally) for _≡_.
can indices be converted to parameters?
If you have propositional equality, then all indices can be converted to parameters, and fixed in constructors using equality proofs.

Pair equality in agda

I have the following code which I want to prove:
data Pair (A : Set) (B : A → Set) : Set where
pair : (a : A) → (B a) → Pair A B
pairEq : (A : Set) → (B : A → Set) → (a : A) → (b₁ b₂ : B a) → (pair {A} {B} a b₁ ≡ pair {A} {B} a b₂) → b₁ ≡ b₂
pairEq A B a b₁ b₂ refl = {!!}
How can I prove this is agda? entering refl leads to an error. How can I work this around?
I done it myself:
data Pair (A : Set) (B : A → Set) : Set where
pair : (a : A) → (B a) → Pair A B
pairEq : (A : Set) → (B : A → Set) → (a : A) → (b₁ b₂ : B a) → (pair {A} {B} a b₁ ≡ pair {A} {B} a b₂) → b₁ ≡ b₂
pairEq A B a .b b refl = refl

How do I use Agda's implementation of delimited continuations?

We can implement a delimited continuation monad in Agda rather easily.
There is, however, no need to, as the Agda "standard library" has an implementation of a delimited continuation monad. What confuses me about this implementation, though, is the addition of an extra parameter to the DCont type.
DCont : ∀ {i f} {I : Set i} → (I → Set f) → IFun I f
DCont K = DContT K Identity
My question is: why is the extra parameter K there? And how would I use the DContIMonadDCont instance? Can I open it in such a way that I'll get something akin to the below reference implementation in (global) scope?
All my attempts to use it are leading to unsolvable metas.
Reference implementation of delimited continuations not using the Agda "standard library".
DCont : Set → Set → Set → Set
DCont r i a = (a → i) → r
return : ∀ {r a} → a → DCont r r a
return x = λ k → k x
_>>=_ : ∀ {r i j a b} → DCont r i a → (a → DCont i j b) → DCont r j b
c >>= f = λ k → c (λ x → f x k)
join : ∀ {r i j a} → DCont r i (DCont i j a) → DCont r j a
join c = c >>= id
shift : ∀ {r o i j a} → ((a → DCont i i o) → DCont r j j) → DCont r o a
shift f = λ k → f (λ x → λ k′ → k′ (k x)) id
reset : ∀ {r i a} → DCont a i i → DCont r r a
reset a = λ k → k (a id)
Let me answer your second and third questions first. Looking at how DContT is defined:
DContT K M r₂ r₁ a = (a → M (K r₁)) → M (K r₂)
We can recover the requested definition by specifying M = id and K = id (M also has to be a monad, but we have the Identity monad). DCont already fixes M to be id, so we are left with K.
import Category.Monad.Continuation as Cont
open import Function
DCont : Set → Set → Set → Set
DCont = Cont.DCont id
Now, we can open the RawIMonadDCont module provided we have an instance of the corresponding record. And luckily, we do: Category.Monad.Continuation has one such record under the name DContIMonadDCont.
module ContM {ℓ} =
Cont.RawIMonadDCont (Cont.DContIMonadDCont {f = ℓ} id)
And that's it. Let's make sure the required operations are really there:
return : ∀ {r a} → a → DCont r r a
return = ContM.return
_>>=_ : ∀ {r i j a b} → DCont r i a → (a → DCont i j b) → DCont r j b
_>>=_ = ContM._>>=_
join : ∀ {r i j a} → DCont r i (DCont i j a) → DCont r j a
join = ContM.join
shift : ∀ {r o i j a} → ((a → DCont i i o) → DCont r j j) → DCont r o a
shift = ContM.shift
reset : ∀ {r i a} → DCont a i i → DCont r r a
reset = ContM.reset
And indeed, this typechecks. You can also check if the implementation matches. For example, using C-c C-n (normalize) on shift, we get:
λ {.r} {.o} {.i} {.j} {.a} e k → e (λ a f → f (k a)) (λ x → x)
Modulo renaming and some implicit parameters, this is exactly implementation of the shift in your question.
Now the first question. The extra parameter is there to allow additional dependency on the indices. I haven't used delimited continuations in this way, so let me reach for an example somewhere else. Consider this indexed writer:
open import Data.Product
IWriter : {I : Set} (K : I → I → Set) (i j : I) → Set → Set
IWriter K i j A = A × K i j
If we have some sort of indexed monoid, we can write a monad instance for IWriter:
record IMonoid {I : Set} (K : I → I → Set) : Set where
field
ε : ∀ {i} → K i i
_∙_ : ∀ {i j k} → K i j → K j k → K i k
module IWriterMonad {I} {K : I → I → Set} (mon : IMonoid K) where
open IMonoid mon
return : ∀ {A} {i : I} →
A → IWriter K i i A
return a = a , ε
_>>=_ : ∀ {A B} {i j k : I} →
IWriter K i j A → (A → IWriter K j k B) → IWriter K i k B
(a , w₁) >>= f with f a
... | (b , w₂) = b , w₁ ∙ w₂
Now, how is this useful? Imagine you wanted to use the writer to produce a message log or something of the same ilk. With usual boring lists, this is not a problem; but if you wanted to use vectors, you are stuck. How to express that type of the log can change? With the indexed version, you could do something like this:
open import Data.Nat
open import Data.Unit
open import Data.Vec
hiding (_>>=_)
open import Function
K : ℕ → ℕ → Set
K i j = Vec ℕ i → Vec ℕ j
K-m : IMonoid K
K-m = record
{ ε = id
; _∙_ = λ f g → g ∘ f
}
open IWriterMonad K-m
tell : ∀ {i j} → Vec ℕ i → IWriter K j (i + j) ⊤
tell v = _ , _++_ v
test : ∀ {i} → IWriter K i (5 + i) ⊤
test =
tell [] >>= λ _ →
tell (4 ∷ 5 ∷ []) >>= λ _ →
tell (1 ∷ 2 ∷ 3 ∷ [])
Well, that was a lot of (ad-hoc) code to make a point. I haven't given it much thought, so I'm fairly sure there's nicer/more principled approach, but it illustrates that such dependency allows your code to be more expressive.
Now, you could apply the same thing to DCont, for example:
test : Cont.DCont (Vec ℕ) 2 3 ℕ
test c = tail (c 2)
If we apply the definitions, the type reduces to (ℕ → Vec ℕ 3) → Vec ℕ 2. Not very convincing example, I know. But perhaps you can some up with something more useful now that you know what this parameter does.

Resources